Phenotypic Variation and Molecular Marker Network Expression of Some Agronomic Traits in Rice (Oryza sativa L.) RILS of Gr 89-1×Shuhui 527 - Lu Gan; Lunxiao Huang; Hongyu Wei; Fei Jiang; Jiajia Han; Jie Yu; Qian Liu; Kunchi Yu; Qiuyu Zhang; Mao Fan; Zhengwu Zhao (Agronomy, 2022)
In this study, a Glutinous rice 89-1 (Gr 89-1) × Shuhui 527 recombinant inbred line population (RIL) comprising 309 F9-generations was used to screen gradient molecular markers. The phenotypic variation and distribution of eight agronomic traits obtained from multiyear and multilocation samples, as well as the network expression relationships between agronomic traits and molecular markers, were investigated. The results showed that there were 14 phenotypic lines with significant differences in the RILs, and the molecular testing results of most of the lines were consistent with the phenotype. The correlation degree between the first-level molecular markers and the eight agronomic traits was 100%. Excluding the correlations of third-level markers with grain width and grain length, the degree of correlation between molecular markers and agronomic traits decreased with an increase in marker levels. The RILs were divided into eight core populations and one approximate population, revealing genetic correspondence between agronomic traits and molecular markers.